Outpatient maternity care and telemedicine use perceptions in the COVID-19 pandemic: a 2020 CERA survey. (28th May 2022) - Foster, Krys E.; Casola, Allison R.; Uzumcu, Zeynep; Wodoslawsky, Sascha; Kelly, Christina
ABSTRACT: The COVID-19 pandemic resulted in rapid telemedicine implementation. This study aimed to identify mean differences in telehealth maternity care provided by perceived patient acceptability and clinician satisfaction, and to determine the association between acceptability, satisfaction, and perceived anticipation of long-term telehealth utilization in family medicine maternity care. Data from the 2020 Council of Academic Family Medicine Educational Research Alliance general membership survey of family medicine educators and practicing clinicians were analyzed. Respondents who reported providing maternity care in the 12 months preceding the survey were included (N = 290). Descriptive statistics were calculated. ANOVA was used to determine the mean difference in percent maternity care provided by reported clinician satisfaction and perceived patient acceptability. Logistic regression models were fit to determine associations between perceived telehealth satisfaction and acceptability with long-term use. The sample was 67 percent female, 85 percent white, mean age of 45 years (SE = .63). 51 percent reported total prenatal visits decreased since pandemic onset. Greater agreement with perceived patient telehealth acceptability (OR = 3.73, 95 percent CI 1.09, 12.71) and clinician telehealth satisfaction (OR = 3.72, 95 percent CI 1.40, 9.86) was significantly associated with anticipated long-term usage. Perceived patient telehealth acceptance and clinician satisfaction were significantly higher among clinicians providing more telehealth and positively associated with anticipated long-term use.